Investigation of the response of equatorial MLTI region during a partial solar eclipse through ground-based daytime optical technique - Vineeth, C.; Pant, T.K.; Thampi, Smitha V.; Sridharan, R.; Ravindran, Sudha; Devasia, C.V.; Kumar, K. Kishore; Alex, S. (My University, 2008)
[1] First experimental evidence for solar eclipse induced changes in the equatorial mesopause and the thermosphere ionosphere regions using daytime optical photometer is presented. The photometer was operated in scanning mode to probe the thermosphere and mesopause regions simultaneously in North-South direction over Trivandrum (8.5°N; 77°E; dip lat. 0.5°N) during a partial solar eclipse event on 03 October 2005. This provided a unique data set of thermosphere and mesopause regions over a horizontal distance of 600 and 240 km respectively from zenith during this event. The striking feature observed during the eclipse is the enhancement in the thermospheric O(1D) 630 nm dayglow intensity and its equatorward movement. Another noteworthy observation is an overall enhancement in the mesopause temperature, more pronounced (∼25–30 K) over zenith. These observations are discussed in context of the vertical coupling of the mesopause with thermosphere-ionosphere region.
Keywords: Equatorial MLTI; Equatorial mesopause; Thermosphere ionosphere; PSMOS; MLTI